2013
DOI: 10.1371/journal.pone.0077256
|View full text |Cite
|
Sign up to set email alerts
|

Zhangfei/CREB-ZF – A Potential Regulator of the Unfolded Protein Response

Abstract: Cells respond to perturbations in the microenvironment of the endoplasmic reticulum (ER), and to the overloading of its capacity to process secretory and membrane-associate proteins, by activating the Unfolded Protein Response (UPR). Genes that mediate the UPR are regulated by three basic leucine-zipper (bLZip) motif-containing transcription factors – Xbp1s, ATF4 and ATF6. A failure of the UPR to achieve homeostasis and its continued stimulation leads to apoptosis. Mechanisms must therefore exist to turn off t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Moreover, both transcriptional activity and DNA recruitment of CREB coactivator CRTC2 on CRE were significantly diminished by SMILE, but not by leucine zipper-mutated SMILE. Consistent with our observation, the short form of SMILE (Zhangfei) has been shown to cause the proteasomal degradation of the basic leucine zipper motif-containing transcription factor Xbp1s in a leucine zipper-dependent interaction (20). We also found that the short form of SMILE inhibited CREB/CRTC2 transcriptional activity (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, both transcriptional activity and DNA recruitment of CREB coactivator CRTC2 on CRE were significantly diminished by SMILE, but not by leucine zipper-mutated SMILE. Consistent with our observation, the short form of SMILE (Zhangfei) has been shown to cause the proteasomal degradation of the basic leucine zipper motif-containing transcription factor Xbp1s in a leucine zipper-dependent interaction (20). We also found that the short form of SMILE inhibited CREB/CRTC2 transcriptional activity (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…While our results clearly identify the leucine zipper of Zhangfei as important for its interaction with p53 and subsequent p53-mediated suppression of the UPR, we have also shown that Zhangfei interacts with the bLZip UPR transcription factor Xbp1s, targeting it for proteosomal degradation, 11 and that the leucine zipper of Zhangfei is also important for this interaction. Hence, modulation of UPR by Zhangfei may require a combination of several coordinated events, including direct interaction with UPR mediators and indirect mediation through p53.…”
Section: Discussionmentioning
confidence: 46%
“…10 Zhangfei also has a profoundly suppressive effect on the unfolded protein response (UPR), at least partly because it targets Xbp1s, an important UPR mediator, for proteasomal degradation. 11 We have detected Zhangfei protein in differentiated neurons, but not in developing neurons or cells of neuronal tumors, 10 nor in osteosarcoma cell lines. The ectopic expression of Zhangfei in several tumor cells lines derived from medulloblastomas (ONS-76, UW228 12 ) and osteosarcomas (D-17 13 ) causes the cells to stop growing and display markers of apoptosis.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“… 45 CREBZF also regulates the unfolded protein response to protect against excessive protein synthesis during endoplasmic reticulum stress. 46 …”
Section: Methodsmentioning
confidence: 99%